Бремя власти: роман / Дмитрий Балашов - Балашов Дмитрий Михайлович (Современник, 1983)
Экземпляры: ф.1 (20190318) / Инвентарный номер: 8085 / Цена: 1.90 / Авт.знак: Б20 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6